Insertion of bacteriophage lambda into the deo operon of Escherichia coli K-12 and isolation of plaque-forming lambdadeo+ transducing bacteriophages. - Buxton, R S (1978)
A procedure has been devised to isolate plaque-forming lambda cI857S7 transducing bacteriophage which carry the internal promoter, P3, of the deo operon of Escherichia coli and the deoB and deoD genes, while lacking the deoP and cytP promoters of the same operon, in order to study, specifically, regulation at the P3 site. This has been accomplished by selecting for the insertion of bacteriophage lambda into the deoA gene in a strain deleted for the normal lambda attachment site (delta att lambda) and isolating from this lysogen lambda spi- and lambda EDTAr phage. Among these, lambda pdeoB+D+ phage were identified by their transducing abilities. From in vivo enzyme induction experiments performed on a delta deo strain lysogenized with such phage, they were shown to carry the P3 promoter while lacking the deoP and cytP promoters. A lambdapdeo B+D+ phage phage was used to lysogenize a deo+ delta att lambda strain, integration of lambda occurring within the region of homology, and, from a heat-induced lysate of this strain, a plaque-forming lambda+ phage carrying the complete deo operon was obtained. Phage lambda was also inserted into the deoB and deoD genes and into the tdk gene. By isolating lambdaspi- and lambdaEDTAr phage from the deo::(lambda) mutants and determining which bacterial genes they carried and whether they retained the int gene of lambda, it was found that lambda had inserted into deoD with the same orientation as lambda inserted into attlambda, whereas lambda inserted into deoA and deoB had the opposite orientation. Deletions extending from the site of lambda insertion into the bacterial chromosome were isolated by selecting for heat-resistant revertants. These confirmed the order of markers to be deo-serB-trpR-thr and also placed a locus, msp, determining sensitivity or resistance of male strains to male-specific phages, between trpR and thr. For some reason unknown, but which may be related to the orientation of the lambda prophages, short deletions rendering the bacterium Ser- Thr+ were of much lower frequency from the deoD::(lambda) lysogen than from the other two lysogens. From an examination of the residual deoD enzyme levels in deoB::(lambda) mutants, it was deduced that there may be two promoter sites within the deoB::(lambda) mutants, it was deduced that there may be two promoter sites within the deoB gene, transcription from one of these being sufficient to account for the noncoordinate nature of the induction of deoB and deoD gene products.